Gallium phosphide nanowires for "biological concentrations" ammonia detection. Issue 1 (1st February 2022) - Kondratev, V M; Kuznetsov, A; Fedina, S V; Nalimova, S S; Moshnikov, V A; Bolshakov, A D
Abstract: Ammonia is widespread chemical compound found both in nature and in human body, and its detection is very important in biology and medicine as well as in environmental monitoring systems. This work is aimed at fabrication and study of precise, technological and relatively cheap ammonia sensors compatible with a liquid medium. Here we use GaP epitaxial nanowires (NWs) as adsorption elements capable of ammonia detection fabricated via a simple protocol. The device properties are studied in terms of change in sensor impedance spectrum upon presence of ammonia. Physical interpretation of the impedance spectra in the presence of water and ammonia is given. GaP–based device exhibit sufficient response to the ammonia presence with the detection limit lower than 2.5 ppm.